(untitled) - Niranjan Rajpurohit (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
An effective management control or strategy execution requires a good leadership. Leaders are the first ones we look up to in times of crisis. There are a few interesting lessons from ancient Indian scriptures as to how different leadership styles can inspire or demotivate employees. The victory of the Pandavas over the Kauravas in the Indian epic ’Mahabharata’, despite superior numbers of the latter, provides interesting insights on what were the reasons for the massive defeat. Leadership emerges as a key factor. In this paper, the author discusses the leadership of Shri Krishna which played a critical role in ensuring the victory of Pandavas and defeat of Kauravas. As an example of poor leadership, author takes the case of King Dhritarashtra. An insight into the leadership styles of the characters in the Mahabharata offers interesting lessons on effective leadership.